Private university policy in formulating the KKNI for islamic religious education - Lola Pitaloka lola; Muh. Wasith Achadi; Yeni Wulandari (At Turots: Jurnal Pendidikan Islam, 2024)
The purpose of this study is to see how the policy of private universities in formulating KKNI, the basic theory related to KKNI explains the statement of the quality of Indonesian Human Resources (HR) whose qualification levels are based on the level of ability stated in the formulation of learning outcomes. Universities as producers of educated HR need to measure their graduates, whether the graduates produced have 'abilities' equivalent to the 'abilities' (learning outcomes) that have been formulated in the KKNI qualification levels. This study uses a Qualitative research method. The data sources used in this study are primary data and secondary data, in the primary data there is an interview with the secretary of LPM STIT Makrifatul Ilmi Bengkulu Selatan, in the secondary data there is KKNI data that has been recorded. This study uses data collection techniques, namely interviews, documentation and observation with data analysis techniques, namely Data Reduction, Data display/data presentation and drawing conclusions on the results of the study in the interview with the secretary of LPM STIT Makrifatul Ilmi Bengkulu Selatan. The work management of LPM is structured, LPM and Quality Group design the mapping of courses, learning outcomes, course achievements and study program achievements and mapping of course studies. But in the concept of campus management, which requires every decision to coordinate with the Makrifatul Ilmi foundation institution, this is what makes the fiqh material courses and fiqh learning in madrasahs not revised as needed because the foundation institution does not give permission to make revisions to the KKNI in conclusion in this study explains the formulation of KKNI at the Makrifatul Ilmi Bengkulu Selatan Tarbiyah College of Science in the conclusion of this study was found in the interview data of the secretary of LPM STIT Makrifatul Ilmi Bengkulu Selatan, that the work management of LPM is structured, LPM and Quality Group design the mapping of courses, learning outcomes, course achievements and study program achievements and mapping of studies.